1992
DOI: 10.1007/bf00588148
|View full text |Cite
|
Sign up to set email alerts
|

Acute traumatic central cord syndrome: MRI-pathological correlations

Abstract: The acute traumatic central cord syndrome (ATCCS) is commonly stated to result from an injury which affects primarily the center of the spinal cord and is frequently hemorrhagic. To test the validity of this widely disseminated hypothesis, the magnetic resonance images [MRI] of 11 consecutive cases of ATCCS caused by closed injury to the spine were analyzed and correlated with the gross pathological and histological features of 3 cervical spinal cords obtained at post mortem from patients with ATCCS, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(113 citation statements)
references
References 15 publications
6
102
0
3
Order By: Relevance
“…13 It is postulated that injury to these large CST axons may form the basis for hand weakness seen in ATCCS. 1,3 In the current study, we have analyzed morphometrically the number of motor neurons at these levels to determine whether injury to the CST, which has been previously documented after ATCCS, 1 results in motor neuron loss in cervical spinal cord segments which supply hand musculature. In the chronic high level injury (C2), the epicenter of injury was furthest away from the motor neurons supplying hand muscles.…”
Section: Discussionmentioning
confidence: 99%
“…13 It is postulated that injury to these large CST axons may form the basis for hand weakness seen in ATCCS. 1,3 In the current study, we have analyzed morphometrically the number of motor neurons at these levels to determine whether injury to the CST, which has been previously documented after ATCCS, 1 results in motor neuron loss in cervical spinal cord segments which supply hand musculature. In the chronic high level injury (C2), the epicenter of injury was furthest away from the motor neurons supplying hand muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these injuries displayed no central hematomyelia but showed preferential di use axonal disruption in the lateral tracts. Quencer 15 in the same study looked only at central cord injuries and again found the same pattern of injury in milder cord traumas. Only the more severely injured spinal cord displayed central hemorrhage.…”
Section: Discussionmentioning
confidence: 69%
“…Studies on monkey spinal cords by Barnard, 10 Nathan, 11 Coxe, 12 and Pappas 13 analyzed the degeneration of selective ®ber tracts from cortex or subcortex and showed that arm ®bers within the corticospinal tract are di usely intermingled with leg ®bers. Bunge 14 and Quencer 15 examined cases of cervical trauma that showed di use axonal loss within lateral columns rather than central injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, the historical report of Schneider et al 1 has been challenged. Not only have the original descriptions of pathogenesis and neuroanatomical basis of TCCS been criticized, [7][8][9][10][11] but optimal treatment of the condition has also been reappraised. 3,[12][13][14][15][16] This survey study challenges the ambiguity of the TCCS definition as introduced by Schneider et al Whereas several physicians assign a diagnosis of TCCS in SCI patients with only 1 motor score point lower in the upper extremities than in the lower extremities, other physicians consider patients with a minimum difference of 15 points as TCCS patients.…”
Section: Discussionmentioning
confidence: 99%